Elevated ALT/AST ratio as a marker for NAFLD risk and severity: insights from a cross-sectional analysis in the United States - Xuan, Yanyan; Wu, Dingting; Zhang, Qin; Yu, Zhiqiang; Yu, Jingbo; Zhou, Dongdong (Frontiers in Endocrinology, 2024)
Background The prevalence and incidence of Nonalcoholic fatty liver disease (NAFLD) are increasing worldwide, and NAFLD has emerged as a prominent global health concern. The link between serum alanine aminotransferase (ALT) to aspartate aminotransferase (AST) ratio and NAFLD remains unclear. This study investigated the association between the ALT/AST ratio and NAFLD prevalence, including liver steatosis and fibrosis levels in the population. Methods We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) 2017–2018, including 4753 participants. Subgroup analyses, stratified by age, gender, and body mass index (BMI), were performed, along with adjusted multivariable logistic regression analyses to evaluate the relationship between ALT/AST levels and the likelihood of NAFLD, liver steatosis, and hepatic fibrosis stage. A generalized additive model examined the non-linear relationship between ALT/AST and the probability of developing NAFLD. Results Among 4753 participants, 1508 (31.73%) were diagnosed with NAFLD. Significant positive correlations between ALT/AST and NAFLD risk were found across all models. In addition, the subgroup analysis by gender, age, and BMI suggested that ALT/AST showed a positive correlation with NAFLD. The ALT/AST ratio was positively correlated with the degree of liver steatosis and liver fibrosis. The correlation between ALT/AST and the incidence of NAFLD showed a non-linear pattern. In women, the non-linear trend is particularly evident, showing an inverted U-shaped curve with an inflection point of 1.302. A receiver operating characteristic (ROC) analysis showed that the predictive value of ALT/AST for NAFLD was better than that of traditional liver enzyme parameters. Conclusion A higher ALT/AST ratio was independently associated with a significantly higher risk of NAFLD and liver fibrosis within American cohorts. This link is robust among females, children, and adolescents. ALT/AST ratio can be used as a simple and effective noninvasive biomarker to identify individuals with high risk of NAFLD.